Risk of Dementia and Community-Based Patient Safety Regarding Health in the Elderly Women - Umi Hani; Indah Wulaningsih; Shindi Hapsari; Fery Agusman Motuho Mendrofa; Tri Ismu Pujiyanto (GLOBAL HEALTH SCIENCE GROUP, 2022)
Multimorbidity is a challenge in elderly women's health. The increased risk of adverse health outcomes associated with frailty is related to patient safety issues, which is need broad community involvement to improve patient safety. This study aimed to describe the cognitive function of menopause women and describe the community empowerment regarding the community-based patient safety. This study was descriptive cross-sectional survey used MMSE, MOCA, and WHO-QOL brief questionnaire. The study participants were conveniently collected from 98 elderly women in nursing home and community in Semarang. A mixed methods analysis of patient safety incidents in the community related to older adults including the basic descriptive statistics and the differences of cognitive function and quality of life after giving the intervention. 87% of women are at risk for mild dementia, with a moderate quality of life for 60%. 73.5% (MMSE) and 71.4% (MOCA-INA) respondents were at mild to moderate level of memory impairment. Community-based doodle art therapy was significantly effective to improve memory index and quality of life. Patient safety that is often reported in female patients is associated with decreased cognitive function. Patient and community involvement can positively influence health outcomes.